2020
DOI: 10.1016/j.scog.2019.100145
|View full text |Cite
|
Sign up to set email alerts
|

Differential improvement of negative-symptom subfactors after cognitive remediation in low-functioning individuals with schizophrenia

Abstract: BackgroundNegative symptoms and cognitive deficits have a substantial predictive value for functional deficits and recovery in schizophrenia. However, the relationship between negative symptoms and cognitive abnormalities is unclear possibly due to the heterogeneity of negative symptoms. This study used the model of expressive and experiential negative symptoms subfactors to decrease this heterogeneity. It examined these subfactors and cognition before and after treatment with computerized cognitive remediatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…One line of research points to cognitive deficits underlying symptoms of this domain (26,28,29). In support of this theory, a stronger association to cognitive deficits for diminished expression than apathy has been shown in some studies of adult patients with schizophrenia, although the overall differences are not large, and not consistent regarding the cognitive domains involved (22,23,30). In the present study of adolescents with EOP, apathy and diminished expression were similarly associated with lower verbal learning performance.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…One line of research points to cognitive deficits underlying symptoms of this domain (26,28,29). In support of this theory, a stronger association to cognitive deficits for diminished expression than apathy has been shown in some studies of adult patients with schizophrenia, although the overall differences are not large, and not consistent regarding the cognitive domains involved (22,23,30). In the present study of adolescents with EOP, apathy and diminished expression were similarly associated with lower verbal learning performance.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, we aimed to (1) explore the factorial structure of the negative symptom construct and (2) investigate associations between cognitive impairments and negative symptom domains in EOP. We hypothesized that two factors of negative symptoms will be identifiable; an apathy factor and a diminished expression factor, and that diminished expression is more strongly associated with cognitive impairments, in accordance with studies of adult patients [e.g., (22,23)].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…A recent metaanalysis (n=309) has provided evidence for an improvement of overall negative symptoms (Cella et al, 2017a), but specific effects for apathy are unfortunately rarely reported. In this regard, post-hoc analyses based on data from a previously reported randomized 12week study with CRT in chronic patients (Lindenmayer et al, 2018) revealed that CRT improved severity of apathy measured with the Positive and Negative Symptoms Scale (PANSS) social amotivation factor (Sevy et al, 2020) (see (Fervaha et al, 2014;Liemburg et al, 2013) for more details on PANSS social amotivation factor). In relation to apathy, cognitive remediation interventions can potentially improve deficits of reward learning, which have been linked to deficits in cognitive functions, in particular, in working memory (Collins et al, 2017).…”
Section: Psychosocial Interventionsmentioning
confidence: 99%